PEMAKNAAN DEMOKRASI DI ERA REFORMASI (OPINI MASYARAKAT JAWA TENGAH TERHADAP DEMOKRASI SAAT INI) - ARIF SOFYAN, ARIF SOFYAN (Politika: Jurnal Ilmu Politik, 2013)
Abstract Political reform affects a lot of changes in the socio-political life of society, both in the political understanding and implementation. This study aims to understand how the understanding and implementation of democratic in Central Java at this time. The study used a descriptive approach to the analysis, and involves about 500 informants in Central Java. The conclusion of this study is that the substance of democracy and its implementation in the community is experiencing a change for a new form, where there is a clash of democratic values ​​which sided constructive and destructive. Democracy constructively interpreted by structuring the system of government, social and political systems, the creation of an atmosphere of equality, freedom of togetherness and involvement of people in decision-making, the use of political procedures that allow broad participation. Democratic forms of destructive behavior such intervention against state institutions, violate the rights of others, and are not tolerant of differences Keywords: democracy, reform, politics